The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf00367103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of different strains of enteropathogens in a lactic-fermenting cereal gruel

Abstract: Twenty-eight strains of enteropathogens, including Campylobacter, Salmonella, Shigella, enterotoxigenic Escherichica coli (ETEC), Staphylococcus and Bacillus were added to cereal gruels prepared from low-tannin sorghum and inoculated with a lactic acid starter culture. Campylobacter strains were not detectable after 6 h, and Salmonella, Shigella and Staphylococcus strains not after 12 h. No viable cells of Bacillus strains were detected after 16 h of fermentation and the ETEC strains were completely inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
2
25
1
1
Order By: Relevance
“…Preliminary investigation of vibriocidal activities of Ogi tutu, V. amygdalina and P. guajava showed in vitro vibriocidal activities. These agreed with findings on antibacterial activities documented in the literature 16,19,[22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Preliminary investigation of vibriocidal activities of Ogi tutu, V. amygdalina and P. guajava showed in vitro vibriocidal activities. These agreed with findings on antibacterial activities documented in the literature 16,19,[22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
“…Ogi-tutu (500 mg/ml) was less effective in treating V. cholerae infection as evidenced by the moderate diffuse degenerative and inflammatory changes observed at histopathology. Ogi-tutu contain lactic acid bacteria (LAB) which have been shown to possess or have antimicrobial potentials and it is significant in the management of human clinical infections [22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the broadly recognized advantages of subjecting food materials to LAB-steered fermentation processes is the inhibitory effect this has on the growth of other microorganisms, especially food-borne pathogens [39,59]. Several previous studies have shown that the growth of members of the Enterobacteriaceae and other bacteria is inhibited by the lactic acid produced during fermentation [1,60].…”
Section: Discussionmentioning
confidence: 99%
“…They are also widely used as starter cultures in the fermentation of sausages and have been used to control food pathogens in vegetables (43). Pediococci have previously been isolated from fermented cereal gruels (22).…”
Section: Discussionmentioning
confidence: 99%